Pembelajaran Daring: Depresi dan Kecemasan Pada Mahasiswa Selama Pandemi COVID-19 - Anggun Budiastuti (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2021)
This study aimed to assess depression and anxiety and to analyze the impact of online learning on depression and anxiety among students. Online-based cross sectional study with snowballing sampling method was conducted among 442 students enrolled at graduate level in universitas sriwijaya. Students were asked to fill out a survey which was available in googleform link shared through whatsapp and others social media platform. The prevalence of depression and anxiety was 40% and 60,1%, respectively, range from mild, moderate and severe symptoms. The study showed significant associatios between online learning and depression (PR=1,79 95% CI 1,15-2,79)and anxiety(PR=1,78 95% CI 1,11-2,87. Based on research findings that showed a high prevalence of depression and anxiety among students during the COVID-19 pandemic, psychological counseling was needed to minimize students mental health risks.